2012
DOI: 10.1038/nature11334
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study indicates two novel resistance loci for severe malaria

Abstract: Malaria causes approximately one million fatalities per year, mostly among African children. Although highlighted by the strong protective effect of the sickle-cell trait, the full impact of human genetics on resistance to the disease remains largely unexplored. Genome-wide association (GWA) studies are designed to unravel relevant genetic variants comprehensively; however, in malaria, as in other infectious diseases, these studies have been only partly successful. Here we identify two previously unknown loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
230
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(246 citation statements)
references
References 26 publications
14
230
1
1
Order By: Relevance
“…Our findings were later confirmed by Okunade and colleagues who generated a similar PMCA4 knockout mouse model [52]. In addition a very recent GWAS study showed the PMCA4 gene to be associated with resistance to infection by malaria plasmodium in humans [53]. Therefore, our discovery that ATA is a specific inhibitor for PMCA4 could have further potential applications in the fields of contraception and anti-malaria treatment.…”
Section: Pmca4 Mutsupporting
confidence: 75%
See 1 more Smart Citation
“…Our findings were later confirmed by Okunade and colleagues who generated a similar PMCA4 knockout mouse model [52]. In addition a very recent GWAS study showed the PMCA4 gene to be associated with resistance to infection by malaria plasmodium in humans [53]. Therefore, our discovery that ATA is a specific inhibitor for PMCA4 could have further potential applications in the fields of contraception and anti-malaria treatment.…”
Section: Pmca4 Mutsupporting
confidence: 75%
“…At higher concentrations (up to 100 μM) ATA has been reported to have several effects on different cell types. For example, ATA has been described as an anti-viral [40][41][42][43][44][45] and anti-apoptotic agent [51][52][53]. It also inhibits several types of nucleases (DNAse I, RNAse A, SI nuclease, exonuclease) [46][47][48].…”
Section: Pmca4 Mutmentioning
confidence: 99%
“…These findings were confirmed by Okunade et al who generated a similar PMCA4 knockout mouse model [24]. In addition, a GWAS has shown the PMCA4 gene to be associated with resistance to infection by malaria plasmodium in humans [25]. These findings have collectively implicated PMCAs in a variety of diseases and have led us to optimise and validate a generic PMCA screening compatible assay to be performed for drug discovery purposes.…”
Section: Introductionsupporting
confidence: 65%
“…Several recent studies found potential associations between SNPs in the ATP2B4 gene, and diseases or disease-related conditions, including reduced bone mass [21], increased incidence of schizophrenia [22], cardiac hypertrophy [23], red blood cell traits [24], and the incidence of malaria infection [25]. In GWAS studies the SNP rs7551442 in the ATP2B4 gene was specifically linked to red blood cell MCHC (mean corpuscular hemoglobin concentration, Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In GWAS studies the SNP rs7551442 in the ATP2B4 gene was specifically linked to red blood cell MCHC (mean corpuscular hemoglobin concentration, Ref. [24]), while SNPs rs2365860, rs10900589, rs2365858 and rs4951074 were linked to malaria infection sensitivity [25]. These conditions may be linked phenotypes, e.g.…”
Section: Discussionmentioning
confidence: 99%